2011
DOI: 10.1111/j.2044-8287.2011.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision making in breast cancer: A longitudinal exploration of women's experiences

Abstract: The findings from this study suggest a need for eliciting more specific psycho-social interactions in the treatment decision-making process in order to identify ways in which women can be supported throughout their experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 56 publications
3
52
0
1
Order By: Relevance
“…Both should increase the likelihood of engaging in decision-making behaviors such as information-seeking, deliberating over benefits and drawbacks of options, clarifying personal values, and ultimately enacting the decision (Gall, 2004;Jenkins & Pargament, 1995). Positive appraisals may also reduce anxiety, an additional barrier to engaging in decision-making behaviors (Swainston et al, 2011;Sweeny et al, 2010). Spirituality as a meaning-making resource has been described as a system of motivational, affective, and cognitive components for making meaning in life (Park, 2007) and may be the ultimate outcome of spiritual coping (Gall et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Both should increase the likelihood of engaging in decision-making behaviors such as information-seeking, deliberating over benefits and drawbacks of options, clarifying personal values, and ultimately enacting the decision (Gall, 2004;Jenkins & Pargament, 1995). Positive appraisals may also reduce anxiety, an additional barrier to engaging in decision-making behaviors (Swainston et al, 2011;Sweeny et al, 2010). Spirituality as a meaning-making resource has been described as a system of motivational, affective, and cognitive components for making meaning in life (Park, 2007) and may be the ultimate outcome of spiritual coping (Gall et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…We found that the vast majority of women reported that the doctor and the patient should make treatment decisions together on an equal basis or that the patient should make the decisions, but strongly consider the doctor's opinion. Some research has suggested that although many women may report a preference for active participation in treatment decisions, they may not perceive they have a choice of treatment options in the context of non-surgical decisions (e.g., with adjuvant therapy decisions) [52, 56], which could explain some of the variation in findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a patient facing a choice of surgeries for early stage breast cancer may come to her physician with a strong preference for a mastectomy because she wants to control her health. 36 Shared decision making provides a framework to discuss her preferences in the context of the available evidence, ensuring that the decision is both in the patient's best interest and consistent with her informed values. Similarly, in the increasingly common situation in which a patient requests treatment that in the clinician's view is not evidence based, shared decision making can uncover the beliefs and values underlying this request and support both the patient and the clinician in conveying their viewpoints.…”
Section: Importance Of Preparing Patientsmentioning
confidence: 99%